2009
DOI: 10.1182/blood-2009-01-200931
|View full text |Cite
|
Sign up to set email alerts
|

A distinguishing gene signature shared by tumor-infiltrating Tie2-expressing monocytes, blood “resident” monocytes, and embryonic macrophages suggests common functions and developmental relationships

Abstract: We previously showed that Tie2-expressing monocytes (TEMs) have nonredundant proangiogenic activity in tumors. Here, we compared the gene expression profile of tumor-infiltrating TEMs with that of tumorassociated macrophages (TAMs), spleenderived Gr1 ؉ Cd11b ؉ neutrophils/myeloidderived suppressor cells, circulating "inflammatory" and "resident" monocytes, and tumor-derived endothelial cells (ECs) by quantitative polymerase chain reactionbased gene arrays. TEMs sharply differed from ECs and Gr1 ؉ Cd11b ؉ cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
390
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 301 publications
(412 citation statements)
references
References 57 publications
22
390
0
Order By: Relevance
“…In other contexts, such as in tumor vascularization, macrophages have been implicated as a source of VEGFA production (11). In this study, we showed that macrophages in the fetal gonad also express Vegfa and, like tumor-associated macrophages (36)(37)(38), express the angiogenic-associated receptors NRP1 and TEK/ TIE2. Macrophages may use these cell-surface receptors to sequester pools of the endothelial attractant factors VEGF or ANGPT and present them to endothelial cells to guide neovascularization of tumors.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In other contexts, such as in tumor vascularization, macrophages have been implicated as a source of VEGFA production (11). In this study, we showed that macrophages in the fetal gonad also express Vegfa and, like tumor-associated macrophages (36)(37)(38), express the angiogenic-associated receptors NRP1 and TEK/ TIE2. Macrophages may use these cell-surface receptors to sequester pools of the endothelial attractant factors VEGF or ANGPT and present them to endothelial cells to guide neovascularization of tumors.…”
Section: Discussionmentioning
confidence: 50%
“…Testis macrophages expressed a number of endothelial markers including Neuropilin 1 (NRP1), which is a vascular endothelial growth factor (VEGF) coreceptor that normally is expressed in endothelial cells but also has been implicated as a marker of macrophages involved in neovascularization of tumors (36)(37)(38) (Fig. S6A); endothelial-specific receptor tyrosine kinase (TEK; also called "TIE2") (Fig.…”
Section: Fetal Gonadal Macrophages Are Localized Near Developingmentioning
confidence: 99%
“…These observations raise the question of whether distinct monocyte/ macrophage subsets found in tumors represent distinct lineages or are rather different differentiation states originated from a common progenitor cell. For example, in the mouse, tumor-infiltrating Tie2-expressing monocytes and blood-circulating resident monocytes share gene expression gene signatures suggesting common developmental relationships and shared functions (Pucci et al, 2009).…”
Section: Phenotypic Heterogeneity Of Monocytes and Tumor Associated Mmentioning
confidence: 99%
“…This has led to the misconception that there are only two types of TAMs. Recent gene expression data from several independent laboratories has discredited this oversimplified idea, showing that TAMs comprise several distinct populations and share properties of both M1 and M2 cells [203][204][205].…”
Section: Box 3: Immune Cell Polarizationmentioning
confidence: 99%